Analysis of Ellipsis in Administrative and Journalistic Style - Chaloupková, Petra (Univerzita Pardubice, 2017)
This bachelor thesis deals with ellipsis and its occurrence in administrative and journalistic style. The paper consists of two parts, the theoretical part and the analysis. In the theoretical part, ellipsis will be defined and classified in terms of recoverability type of ellipsis and its position within a construction. Moreover, the attention will be also drawn to ellipted sentence elements and their possible combinations. The analytical part subsequently studies the types and frequency of ellipsis identified within the administrative and journalistic style. The task of the analysis is to find out which type of ellipsis is preferred in the particular style.
Analysis of ellipsis in the selected texts
Analýza výskytu elipsy v administrativním a žurnalistickém stylu
Keywords: elipsa; gramatická koheze; koordinace; administrativní styl; žurnalistický styl; ellipsis; grammatical cohesion; coordination; administrative style; journalistic style